2023
DOI: 10.1021/acsami.2c18530
|View full text |Cite
|
Sign up to set email alerts
|

Pr-Doped SrTi0.5Mn0.5O3−δ as an Electrode Material for a Quasi-Symmetrical Solid Oxide Fuel Cell Using Methane and Propane Fuel

Abstract: The use of identical electrodes for both the cathode and the anode in a symmetrical solid oxide fuel cell (SSOFC) can simplify the preparation process and increase the durability of the cell, but it is also demanding on the properties of the electrode including stability, electric conductivity, and electrocatalysis. The doping of variable-valence Mn 4+/3+2+ on the B site of stable SrTiO 3 is explored in this study as both the cathode and the anode for an SSOFC. Though the limit of Mn doping in SrTiO 3 is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The O 1s XPS spectra of PS30C-O and PS30C-R (Figure a) showed that their oxides split into three binding energy (BE) peaks at 528.7, 531.2, and 532.7 eV. The BE peak at 528.7 eV is attributed to lattice oxygen (M–O), the BE peak at 531 eV is oxygen vacancy, and in the vicinity of 532.7 eV is the carboxyl group. , The BE peaks of Pr 3d spectra (Figure b) at 932.4 and 953.0 eV may be associated with the presence of Pr 4+ and the BE peaks at 927.9 and 948.4 eV may be attributed to Pr 3+ , and the BE peak at 957.2 eV indicates extra-structure, which is present only in the 3d 3/2 form . The Pr 3+ /(Pr 4+ + Pr 3+ ) of the PS30C-R sample was 0.38, which was greater than the PS30C-O (0.24) because a portion of Pr 4+ was reduced to Pr 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…The O 1s XPS spectra of PS30C-O and PS30C-R (Figure a) showed that their oxides split into three binding energy (BE) peaks at 528.7, 531.2, and 532.7 eV. The BE peak at 528.7 eV is attributed to lattice oxygen (M–O), the BE peak at 531 eV is oxygen vacancy, and in the vicinity of 532.7 eV is the carboxyl group. , The BE peaks of Pr 3d spectra (Figure b) at 932.4 and 953.0 eV may be associated with the presence of Pr 4+ and the BE peaks at 927.9 and 948.4 eV may be attributed to Pr 3+ , and the BE peak at 957.2 eV indicates extra-structure, which is present only in the 3d 3/2 form . The Pr 3+ /(Pr 4+ + Pr 3+ ) of the PS30C-R sample was 0.38, which was greater than the PS30C-O (0.24) because a portion of Pr 4+ was reduced to Pr 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Doping with high-valence elements is regarded as an effective approach to stabilize the structure of perovskites. [23][24][25] For instance, Li et al proposed a co-doped composition, Ba 0.95 La 0.05 Fe 0.9 Nb 0.1 O 3−d , for use as the electrodes of symmetric SOFCs, exhibiting remarkable structural stability against wet H 2 -reduction, which is attributed to the considerably high valence state of Nb. 24 Furthermore, the redox couple Mo 6+ /Mo 5+ is commonly employed as a dopant to achieve structural stability, owing to its variable valence in different atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a quasi-symmetric conguration has been studied for solid oxide cells (Q-SSOCs), where two similar electrode materials are optimally combined to further enhance the electrochemical performance of SSOCs. 15,16 This conguration can also be obtained via a follow-up process aer electrode fabrication, such as annealing in a reducing atmosphere. 17,18 A perovskite oxide (ABO 3 ) can be employed as the effective electrode material for an SOC since it has mixed ionic and electronic conducting (MIEC) and redox-stable properties depending on its versatile combinations of A/B cations.…”
Section: Introductionmentioning
confidence: 99%